Ein Primus der Sinnstiftung: Die Riverside Church. Wie eine amerikanische Kirche arbeitet und wirtschaftet - Katrin Gillwald (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
– The author describes the program and organization of the Riverside Church & Corporation in New York City for a German readership, taking German experiences with religious work and life into account. The essay is based on the underlying sociological concept of “welfare production,” which deals with the general question of how societal actors contribute to the quality of life and well-being of people. The first section, “Die Kirche und die Firma” (The Church and the Firm), is a standard introduction of the article's subject. It acquaints the reader with Riverside's neighborhood and buildings, denomination, corporate indicators, and the diversity of its congregation. It also includes a brief portrait of its present senior minister, Rev. Dr. James A. Forbes, Jr. This section illustrates the dual nature of U.S. churches as both religious and entrepreneurial organizations. The second section, “Riverside's Angebot—Seelsorge im größeren Zusammenhang” (What Riverside Offers—Pastoral Care Within a Wider Context) explores the mission, goals and day-to-day activities of the Riverside Church. The main topics are its integrative approach known as the “three i's” (interdenominational—interracial—international) and its broad program which centers on worship services and spiritual exercise, including a range of social, cultural, and political activities. The third section, “Der Sonntagsgottesdienst” (The Sunday Worship Service) comprises a description of three frequently mentioned elements to make the worship services of the Riverside Church particularly attractive: the famous sermons of Reverend Dr. Forbes, the church's music program, and the optical setting. The section closes with observations and explanations of the offertory formalities during the Sunday worship services. The fourth section, “Der Einfluß von Rockefeller und Fosdick” (The Impact of Rockefeller and Fosdick) reviews the founding phase of Riverside and the meeting and synergies of its founding fathers, Dr. Harry E. Fosdick and Mr. John D. Rockefeller, Jr. The author argues that these two men exerted lasting positive influence on Riverside's philosophy, freedom of spirit and action, innovative capacity, and high standing. The fifth section, “Die Ökonomie von Riverside: Das `dreifache t'” (The Economy of Riverside, Including the Three t's”) gives an overview of Riverside's resources. The “Rockefeller endowment” and the time, talent, and treasure of the congregation are emphasized as the financial assets and human input of Riverside's work. Highlights of this section are creative money-making, exemplified by the Easter Flower List, and the New Members Plus Program. The final section, “Die dauernde Herausforderung” (The Constant Challenge) focuses on two main challenges for the Riverside Church & Corporation: the cohesion of its multifaceted congregation, and organizational sustainability in the face of external pressure. The author concludes that Riverside is fit for survival thanks to a timely pastoral concept, professional excellence, business acumen, creativity, ability and willingness to communicate, and innovative capacity.
Keywords: 300; Kirche; Nonprofit-Management; Erfolgsfaktor; USA